Early Symptom Improvement and Discontinuation of 5-α-Reductase Inhibitor (5ARI) Therapy in Patients With Benign Prostatic Hyperplasia (BPH). (March 2014) - Kruep, Eric J.; Phillips, Emily; Hogue, Susan; Eaddy, Michael
Background: Pharmacological treatment options for benign prostatic hyperplasia (BPH) commonly include α-blocker (AB) and 5-α-reductase inhibitor (5ARI) agents, which have separate but important attributes that carry clinical implications in terms of improvement of lower–urinary tract symptoms (LUTS) and clinical disease progression.Objectives: This study hypothesized that administering AB therapy concomitantly with newly started 5ARI treatment would reduce the likelihood of 5ARI discontinuation through early symptom improvement.Methods: This retrospective analysis of the PharMetrics Integrated Medical and Pharmaceutical Database included men aged ≥50 years with ≥1 medical claim of BPH diagnosis and ≥1 prescription claim of a 5ARI with or without an AB. Patients initiating 5ARI monotherapy were propensity score matched with patients initiating combination AB + 5ARI therapy (1:1), with 5ARI time to discontinuation (30-day gap in treatment) compared between groups utilizing survival analysis techniques. The percentage of patients adherent to 5ARI therapy based on medication possession ratio (MPR) was assessed.Results: After 180 days of follow-up, 61.7% of the combination therapy arm versus 59.2% of the monotherapy arm remained on therapy. Combination therapy patients were 10% less likely to discontinue 5ARI treatment (hazard ratio = 0.904; P = .006) and were more likely to be adherent when adherence was defined as MPR ≥70% and ≥75%.Conclusions: Based on an assessment of claims data, initiating AB with 5ARI therapy is associated with a lower rate of 5ARI discontinuation compared with 5ARI monotherapy. Early symptom relief from AB therapy may contribute to a lower discontinuation rate for concomitant 5ARI therapy.